BOOSTING STUDENTS’ EXCITEMENT DURING LONG ONLINE COURSE USING COMBINATION OF ONLINE COURSE PLATFORMS AND SOCIAL MEDIA BASED ASSIGNMENTS - Muhfizaturrahmah Muhfizaturrahmah; Yulieda Hermaniar; Yasyir F. Mubaraq (JPTE FT UNY, 2021)
ABSTRACT:Months of online courses create students’ boredom leading to their decreasing involvement on teaching and learning process. This paper reports how social media based assignment such as Instagram, Whatsapp, and Youtube fills the void and bring back students’ courage to a better level during covid19 lockdown. This is a qualitative study using narrative approach which data was collected collaboratively during even semester of 2019 at English Courses of Department of Electrical Engineering Education Yogyakarta State University and Study Program of English Literature STKIP PGRI Banjarmasin. The data carried from multiple e-learning applications indicates that the more we adopt social media based assignment, the more students were engaged into the class activities and the higher level of involvement was observed.ABSTRAK:Pembelajaran online yang berlangsung selama berbulan-bulan memicu kebosanan peserta didik yang menyebabkan penurunan keikutsertaan mereka dalam proses belajar mengajar. Penelitian ini bertujuan untuk mengetahui bagaimana tugas berbasis media sosial seperti Instagram, Whatsapp, dan Youtube dapat mengisi kekosongan dan mengembalikan keberanian peserta didik menjadi lebih aktif selama lockdown covid19. Penelitian ini merupakan penelitian kualitatif dengan pendekatan naratif yang datanya dikumpulkan secara kolaboratif selama semester genap tahun 2019 pada mata kuliah Bahasa Inggris di Jurusan Pendidikan Teknik Elektro, Universitas Negeri Yogyakarta dan Program Studi Bahasa Inggris STKIP PGRI Banjarmasin. Data yang dihasilkan dari beberapa aplikasi e-learning menunjukkan bahwa semakin kita mengadopsi tugas berbasis media sosial, semakin banyak peserta didik yang terlibat dalam kegiatan kelas dan tingkat keikutsertaan menjadi lebih tinggi.